Development of a Process-Oriented Guided Inquiry Learning (POGIL)- Based Learning Module on Buffer Solutions for Grade XI Senior High School Students - Ramadhani, Adilla Putri; Mawarnis, Elvy Rahmi (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study developed a Process-Oriented Guided Inquiry Learning (POGIL)-based printed learning module on buffer solutions for Grade XI senior high school students. The novelty of this study lies in the development of a printed self-instructional POGIL-based module on buffer solutions. This study employed a Research and Development (R&D) approach using the 4-D development model (Define, Design, Develop, and limited Dissemination). Data were collected through expert validation and practicality testing involving Grade XI students and a chemistry teacher. The validation results indicated that the module achieved a material validity score of 83% (Highly valid), a language validity score of 100% (Highly valid), and a construction/graphical validity score of 76% (valid). The practicality test conducted with students yielded a score of 84%, indicating that the module was very practical. In addition, interviews with the chemistry teacher confirmed that the module was practical and efficient for classroom implementation. These findings indicate that the developed module is valid, practical, and suitable for use as an instructional material to support both classroom learning and students’ independent learning.